2018
DOI: 10.1371/journal.pone.0200470
|View full text |Cite
|
Sign up to set email alerts
|

Association of maternal uric acid and cystatin C serum concentrations with maternal and neonatal cardiovascular risk markers and neonatal body composition: The Ulm SPATZ Health Study

Abstract: PurposeIn utero exposure to cardiometabolic risk factors may determine health related outcomes at birth and in later life. The aim of this analysis was to describe the relationship of maternal serum uric acid (SUA) and cystatin C with maternal and neonatal cardiometabolic risk markers and with birth weight and risk of small-for-gestational age (SGA) as well as large-for gestational age (LGA).Material and methodsIn the Ulm SPATZ Health Study, 934 singleton newborns and their mothers were recruited during their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“… 8 By contrast, in a recent study of 885 pregnant women from Germany, Rothenbacher et al indicated that maternal increased CysC levels (Q4) were associated with an increased risk for LGA and a decreased risk for SGA compared to Q1 (for LGA, OR = 5.92, 95% CI: 2.27, 15.44; for SGA, OR = 0.35, 95% CI: 0.16, 0.77), and there was no association between UA and birth weight. 10 In our cohort study, the associations between high CysC levels and an increased risk of LGA and between high UA levels and an elevated risk of SGA were extended to the Chinese population. Previous reports suggested that women with GDM had a higher incidence of LGA compared to those without pregnancy complications among individuals who underwent serum screening for Down syndrome (25.82% vs 13.80%) or noninvasive prenatal screening (29.7% vs 18.6%).…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“… 8 By contrast, in a recent study of 885 pregnant women from Germany, Rothenbacher et al indicated that maternal increased CysC levels (Q4) were associated with an increased risk for LGA and a decreased risk for SGA compared to Q1 (for LGA, OR = 5.92, 95% CI: 2.27, 15.44; for SGA, OR = 0.35, 95% CI: 0.16, 0.77), and there was no association between UA and birth weight. 10 In our cohort study, the associations between high CysC levels and an increased risk of LGA and between high UA levels and an elevated risk of SGA were extended to the Chinese population. Previous reports suggested that women with GDM had a higher incidence of LGA compared to those without pregnancy complications among individuals who underwent serum screening for Down syndrome (25.82% vs 13.80%) or noninvasive prenatal screening (29.7% vs 18.6%).…”
Section: Discussionmentioning
confidence: 72%
“…7–9 In a recent study of 885 mothers and their singleton newborns, Rothenbacher et al showed an inverse correlation of maternal high UA with a reduced risk of SGA in an age-adjusted analysis. 10 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, cystatin C was found to be negatively associated with SGA with an odds ratio [OR ] of 0.35 [95% CI: 0.16±0.77 ]. [28] Another case-control study was performed by SK Srinivas, AG Edlow, PM Neff, MD Samme, CM Andrela1 and MA Elovitz et al . Cases were patients with preeclampsia.…”
Section: Discussionmentioning
confidence: 99%
“…Different tests and parameters, including uric acid are being carried out in 2nd or 3rd trimester of pregnancy as a predictor of preeclampsia. 4 One study found that frequency of low birth weight was 36.2% in women having hyperuricemia & hypertension during pregnancy. 5 Study carried by Ryu et al mean uric acid level was 5.8 ranging from (4.7 -6.6) in pre-eclamptic women compared to 3.9 and ranging from (3.1 -4.6) in patients with normal blood pressure.…”
Section: Introductionmentioning
confidence: 99%